Prediction method of hydrofoil vortex shedding frequency at high Reynolds numbers - Hou Lei; Ding Yunfeng; Wang Qing; Zong Zhi; Sun Lei; Jiang Yichen (Zhongguo Jianchuan Yanjiu, 2019)
[Objectives] Flow around hydrofoils under high Reynolds number is always a hot topic in hydrodynamic field due to its complicated principle and difficult calculation. The Discrete Vortex Model (DVM) based on vorticity and stream function formulation is a meshless method,which effectively overcomes the numerical viscous problem. Vortex movement in the flow field with high Reynolds number can also be accurately simulated because of its high resolution in the vortex concentration range. A random vortex method was used to predict the vortex shedding frequency of two-dimensional rigid hydrofoils with high Reynolds number.[Methods] Taking NACA 66 series hydrofoil as an example,the prediction of the frequency was verified by comparing with the experimental data. In addition,the effects of flow velocity and Angle of Attack(AOA) on the frequency of hydrofoil vortex shedding were also discussed and analyzed.[Results] The results show that,the frequency of the vortex shedding increases nonlinearly with the growth of the inflow velocity. And with the increase of the initial AOA of hydrofoil,the size and strength of the vortex rise up and the frequency of the vortex shedding goes down.[Conclusions] The velocity of incoming flow and the initial AOA of hydrofoil have a significant effect on the vortex shedding frequency of two-dimensional hydrofoils,which provide reference for the study on the vortex shedding mechanism of 2D profile of the blade,and even the prediction of the vibration noise of the whole propeller.